Dielectric and AC conductivity studies of novel porous armalcolite nanocomposite-based humidity sensor - Tripathy, Ashis; Pramanik, Sumit; Manna, Ayan; Radzi, Zamri; Abu Osman, Noor Azuan (Wiley, 2017)
Armalcolite, a current motivated rare earth ceramic usually available in the moon, had been used for the first time, as dielectric-type humidity sensors. The armalcolite nanocomposite was prepared using multistep solid-state sintering under high pressure and a high-sensitive dielectric sensor was developed for humidity controlling applications. Different concerning phases developed by the proper sintering were analyzed precisely by X-ray diffraction (XRD) as well as scanning electron microscopy (SEM). At 100 Hz frequency, the obtained dielectric constant was 24 times greater at 95% relative humidity (RH) as compared to 33% RH. The armalcolite-based sensor showed lower hysteresis (<3.5%), good stability, and faster response (~18 seconds) and recovery (~35 seconds) times compared to conventional humidity sensors. The sensing mechanism of the nanocomposite was categorically determined by the analyzed characteristics parameters such as dielectric constants, normalized loss tangent, and alternating current conductivity properties. This study also confirmed that the whole conduction mechanism was accomplished by electrons or ions and dipoles in the entire RH range. Therefore, the present armalcolite-based porous nanocomposite would be a potential sensing material for novel humidity sensors.